2003
DOI: 10.1046/j.1365-2648.2003.02557.x
|View full text |Cite
|
Sign up to set email alerts
|

Swedish nursing students' attitudes to and awareness of research and development within nursing

Abstract: Nursing students had an overall positive attitude towards nursing research and their interest in a particular development or research area was the most important variable for their attitudes and expected use of nursing research in the future. Therefore, it would seem to be important to encourage the students' interest in specific development/research areas of nursing during their education. In spite of the nursing students' positive attitudes to nursing research, the study demonstrates the theory-practice gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
20

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 26 publications
5
40
0
20
Order By: Relevance
“…Ancak hemşire öğrencilerin bu konudaki davranış ve farkındalığına yönelik yapılan çalışmaların yetersiz olduğu bilinmektedir 13 . Hemşireler özellikle lisans eğitimleri sırasında araştırma için gerekli becerileri, değerleri ve hemşirelik uygulamaları için gerekli olan sorgulama yetisini kazanırlar 23 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Ancak hemşire öğrencilerin bu konudaki davranış ve farkındalığına yönelik yapılan çalışmaların yetersiz olduğu bilinmektedir 13 . Hemşireler özellikle lisans eğitimleri sırasında araştırma için gerekli becerileri, değerleri ve hemşirelik uygulamaları için gerekli olan sorgulama yetisini kazanırlar 23 .…”
Section: Discussionunclassified
“…Bu araştırmada öğrencilerin %17.8'i, Björkström ve diğ. 'nin çalışmasında öğrencilerin %25'i hiç bilimsel hemşirelik dergisi okumadığını belirtmiştir 13 . Bu araştırmada mesleki dergi okuyanların araştırma, geliştirme konusunda okumayanlara göre daha fazla farkındalığa ve olumlu tutumlara sahip oldukları belirlenmiştir (p<0.01) (Tablo 2).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Students emphasized this lack of motivation emanated from not expecting to study research, and having a poor understanding of the nature and usefulness of nursing research [5] . However, more positive perceptions of research were evident in the findings of a study carried out by Bjorkstrom, Johnasson, Hamrin, and Athlin [6] . These researchers used a questionnaire to assess Swedish nursing students' attitudes toward research and found that most of the nursing students in their study viewed research positively with 60% expecting to use research in their daily work [6] .…”
Section: Introductionmentioning
confidence: 99%